Myths of Demilitarization in Postrevolutionary Mexico, 1920-1960 - Rath, Thomas G. (Book collections on Project MUSE., 2013)
At the end of the Mexican Revolution in 1920, Mexico's large, rebellious army dominated national politics. By the 1940s, Mexico's Institutional Revolutionary Party (PRI) was led by a civilian president, and claimed to have depoliticised the army and achieved the bloodless pacification of the Mexican countryside through land reform, schooling, and indigenismo. However, this book argues, Mexico's celebrated demilitarisation was more protracted, conflict-ridden, and incomplete than most accounts assume.